تقييم درجة الشّمول المالي المدفوع بابتكارات الموجة الأولى للتّكنولوجيا الماليّة في القطاع المصرفي الجزائري خلال الفترة (2011-2021): Assessment of the degree of financial inclusion driven by the first wave of financial technology innovations in the Algerian banking sector during the period(2011-2021) - بوزانة أيمن; وفاء حمدوش (Journal of North African Economies, 2025)
This study aimed to assess the degree of financial inclusion driven by the first wave of fintech innovations in the Algerian banking sector during the period 2011-2021. In response to the problem, we relied on the analytical descriptive approach,. The study concluded that the role of the banking sector in promoting financial inclusion of all segments of society is very limited as bank brokerages provided do not cover the needs of individuals and institutions and limited only to specific groups, which has widened the financial inclusion gap between the two components of the same category In the absence of a digital banking culture in Algerian society, which is reflected in the low demand for banking cards, ATMs and mobile and Internet vendors